Spontaneous dissociation of H2 and high energy barrier of H invasion on W doped Al2O3(0001) surface. (5th January 2022) - Long, Qian; Guo, Chunsheng; Xin, Xiaojun; Ding, Rui; Luo, Laima; Zhang, Xin; Li, Heng; Cui, Zilin; Xu, Yuhong; Tang, Changjian
Abstract: In view of the wide use of tungsten in fusion experimental devices and the importance of hydrogen isotopes permeation, here we studied the adsorption, dissociation, diffusion and invasion behavior of hydrogen on W doped α-Al2 O3 (0001) surface. Based on the first-principle approaches, we found the W substitution for a top surface Al atom is the most energetically favorable. H2 molecule prefers to be adsorbed on the surface W and spontaneously dissociates into two H anions. Near the W defects, H atoms favor to be adsorbed at the W and Al sites rather than O sites on the surface, and within the subsurface layer H can only bond to W stably. As a result, H migration to subsurface should occur around W with an energy barrier as large as 4.22 eV which is much larger than the 1.91 eV around the O atom on undoped α-Al2 O3 (0001) surface. These findings suggest that W surface doping is beneficial to α-Al2 O3 as tritium permeation barrier. Highlights: Tungsten doping promotes spontaneous dissociation of H2 on α-Al2 O3 surface. H atoms prefer to be adsorbed at W site and hardly to diffuse to surface O or to Al sites. H migration to subsurface should occur around W. Energy barrier of H invasion on W doped surface is much higher than the undoped α-Al2 O3 (0001) surface.